Infecciones en el paciente con trasplante de órganos sólidos - Fica C., Alberto (Revista Hospital Clínico Universidad de Chile, 2007)
Infections in patients with solid organ transplants are associated to disease, death, hospitalization, increased costs and allograft rejection. Several agents are involved and they are distributed sequentially in 3 stages. In the first period, nosocomial and postoperative infectious complications are the hallmark and this stage last in average one month. After that, an opportunistic stage isclassically observed that usually extends to the six month and is explained by an intensive immune suppression. Finally, during the last stage opportunistic infections are progressively replaced by community-acquired morbidities. Microorganisms involved in infectious complications include virus, bacteria, fungi and parasites and there is a vast range of clinical syndromes associated to these agents. This profile implicates a high index of clinical suspicion, comprehensive laboratory resources and a wide drug armamentarium. Several preventive measures are needed in these patients, and include education about food and beverages, animal handling, travelingprecautions, vaccines in selected cases, and chemoprophylaxis.